PENGARUH AKUPUNKTUR TELINGA TERHADAP PENURUNAN TEKANAN DARAH - Joko Tri Haryanto; Purwanto; Chusnul Zulaika; Eka Deviany Widyawaty (Jurnal Medicare, 2025)
Background: Hypertension is one of the major global health problems with an increasing prevalence. According to the World Health Organization (WHO), the number of individuals with hypertension rose from 594 million in 1975 to 1.13 billion in 2019. One of the complementary therapies widely used in hypertension management is auricular acupuncture, which is believed to modulate the autonomic nervous system and reduce blood pressure. This study aims to determine the effectiveness of auricular acupuncture therapy in lowering blood pressure. Methods: This study employed a Quasi-Experimental design with a Pretest–Posttest One Group approach. The research was conducted from February to April 2025 involving 30 respondents selected through purposive sampling. All participants received auricular acupuncture therapy, and blood pressure was measured before and after the intervention. Data were analyzed using the Wilcoxon test to assess differences in pre- and post-intervention blood pressure. Results: The Wilcoxon test showed a significance value of p < 0.05 (p = 0.001), indicating a significant decrease in blood pressure after the administration of auricular acupuncture therapy. Conclusion: Auricular acupuncture therapy is proven to be effective in reducing blood pressure and can be recommended as a complementary therapy in the management of hypertension.